Monitoring the impact of COVID-19 in Myanmar: Rice millers – November 2020 survey round - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
To understand how Myanmar’s rice value chain has been affected by the COVID-19 crisis, a series of phone interviews is being conducted with rice millers from Ayeyarwady, Bago, and Yangon. This report presents data from interviews conducted in November 2020.